Progress regarding the context-of-use of tau as biomarker of Alzheimer's disease and other neurodegenerative diseases. (2nd January 2021) - Campese, Nicole; Palermo, Giovanni; Del Gamba, Claudia; Beatino, Maria Francesca; Galgani, Alessandro; Belli, Elisabetta; Del Prete, Eleonora; Della Vecchia, Alessandra; Vergallo, Andrea; Siciliano, Gabriele; Ceravolo, Roberto; Hampel, Harald; et al.
ABSTRACT: Introduction : Tau protein misfolding and accumulation in toxic species is a critical pathophysiological process of Alzheimer's disease (AD) and other neurodegenerative disorders (NDDs). Tau biomarkers, namely cerebrospinal fluid (CSF) total-tau (t-tau), 181-phosphorylated tau (p-tau), and tau-PET tracers, have been recently embedded in the diagnostic criteria for AD. Nevertheless, the role of tau as a diagnostic and prognostic biomarker for other NDDs remains controversial. Areas covered : We performed a systematical PubMed-based review of the most recent advances in tau-related biomarkers for NDDs. We focused on papers published from 2015 to 2020 assessing the diagnostic or prognostic value of each biomarker. Expert opinion : The assessment of tau biomarkers in alternative easily accessible matrices, through the development of ultrasensitive techniques, represents the most significant perspective for AD-biomarker research. In NDDs, novel tau isoforms (e.g. p-tau217) or proteolytic fragments (e.g. N-terminal fragments) may represent candidate diagnostic and prognostic biomarkers and may help monitoring disease progression. Protein misfolding amplification assays, allowing the identification of different tau strains (e.g. 3 R- vs . 4 R-tau) in CSF, may constitute a breakthrough for the in vivo stratification of NDDs. Tau-PET may help tracking the spatial-temporal evolution of tau pathophysiology in AD but its application outside the AD-spectrum deserves further studies.